INZ‐701, a recombinant ENPP1 enzyme, prevents ectopic calcification in an Abcc6−/− mouse model of pseudoxanthoma elasticum. Issue 7 (16th May 2022) - Jacobs, Ida Joely; Cheng, Zhiliang; Ralph, Douglas; O'Brien, Kevin; Flaman, Lisa; Howe, Jennifer; Thompson, David; Uitto, Jouni; Li, Qiaoli; Sabbagh, Yves
Abstract: Pseudoxanthoma elasticum (PXE), a heritable multisystem ectopic calcification disorder, is predominantly caused by inactivating mutations in ABCC6 . The encoded protein, ABCC6, is a hepatic efflux transporter and a key regulator of extracellular inorganic pyrophosphate (PPi). Recent studies demonstrated that deficiency of plasma PPi, a potent endogenous calcification inhibitor, is the underlying cause of PXE. This study examined whether restoring plasma PPi levels by INZ‐701, a recombinant human ENPP1 protein, the principal PPi‐generating enzyme, prevents ectopic calcification in an Abcc6 −/− mouse model of PXE. Abcc6 −/− mice, at 6 weeks of age, the time of earliest stages of ectopic calcification, were injected subcutaneously with INZ‐701 at 2 or 10 mg/kg for 2 or 8 weeks. INZ‐701 at both doses increased steady‐state plasma ENPP1 activity and PPi levels. In the 8‐week treatment study, histopathologic examination and quantification of the calcium content in INZ‐701‐treated Abcc6 −/− mice revealed significantly reduced calcification in the muzzle skin containing vibrissae, a biomarker of the calcification process in these mice. The extent of calcification corresponds to the local expression of two calcification inhibitors, osteopontin and fetuin‐A. These results suggest that INZ‐701 might provide a therapeutic approach for PXE, a disease with high unmet needs and no approved treatment.